Blockchain applications beyond cryptocurrency: a focus on decentralized markets and contract management - MasrinaNadiaMohd Salleh; Robaisya Rahmat; Shaliza Alwi; Ahmad Aizuddin Hamzah; Tan Say Peng; Saadiah Kaspin (IEEE Xplore, 2023)
Ever since the introduction of Bitcoin, the first and largest cryptocurrency, blockchain technology has successfully made a name for itself as the foundation of digital currencies. It wasn't just used to decentralize money and payments. It is also used to decentralize markets more generally. All types of contracts can be registered, confirmed and transmitted to other network participants via a distributed ledger powered by blockchain technology. This research offers a thorough review of cutting-edge blockchain-related applications that have been written about in the literature. Based on their contributions to the pool of knowledge around blockchain, several published books have been thoughtfully included. We will discuss and go through some ideas in the paper's final portion.